Lipids regulate P2X7-receptor-dependent actin assembly by phagosomes via ADP translocation and ATP synthesis in the phagosome lumen - Kuehnel, Mark. P. (2015)
Latex bead phagosomes isolated from J774 macrophages polymerize actin. We show here that five lipids phosphatidylinositol-4-phosphate, phosphatidylinositol-(4,5)bisphosphate, sphingosine-1-phosphate (S1P), ceramide-1-phosphate and phosphatidic acid - stim. - Fundacao para a Ciencia e a tecnologia (FCT). - We would like to thank Sabrina Marion and Simi Antony for their technical support. We greatly appreciate the suggestions by Jens Reich and Thomas Dandekar. Thanks also to Christopher Bleck for preparing Fig. 4 and to Luis Mayorga, Sabrina Marion and Maxim